Ex 8.4, 3 Simplify. (ii) (𝑎^2+5) (𝑏^3+3)+5Here, there are 2 expressions: 1st expression = (𝑎^2+5) (𝑏^3+3) 2nd expression = 5 Solving 1st expression (𝒂^𝟐+𝟓) (𝒃^𝟑+𝟑) = 𝑎^2 (𝑏^3+3)+5(𝑏^3+3) = (𝑎^2×𝑏^3 )+(𝑎^2×3)+(5×𝑏^3 )+(5×3) = 𝒂^𝟐 𝒃^𝟑+𝟑𝒂^𝟐+𝟓𝒃^𝟑+𝟏𝟓 Now, our expression is (𝒂^𝟐+𝟓) (𝒃^𝟑+𝟑)+𝟓 = 𝑎^2 𝑏^3+3𝑎^2+5𝑏^3+15+5 = 𝒂^𝟐 𝒃^𝟑+𝟑𝒂^𝟐+𝟓𝒃^𝟑+𝟐𝟎

Go Ad-free
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.